International Visitor to the Faculty of Social Sciences : University of New Mexico, 14 June 2013 - Sharifah S., Wan Ahmad (Faculty of Social Sciences, 2013)
The Head of Department of Anthropology and Sociology (ANSOS) was approached by Dr Ziarat Hossein, from the Department of Individual, Family and Community Education, University of New Mexico, on a potential visit to the Faculty of Social Sciences by the undergraduate students of the department. Upon discussion with other members in the ANSOS department, it was agreed that the visit would be of mutual interests for both departments in order to initiate a network with a view to explore the possibility for further cooperation in relevant academic activities.